The Representation of Women in the Musical Imaginary: Analysis of the most Viewed Video Clips in the International and Spanish Context - Canorea-Tiralaso, Héctor; Paz-Gil, Iria; Rajas, Mario (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The video clip is the most widely consumed audiovisual format today and is particularly popular with young people. These videos offer content full of stereotypes, including gender stereotypes. It is therefore of particular interest to analyse the image of women portrayed in these clips. Therefore, the 300 most viewed video clips worldwide and the 300 music videos of Spanish origin with the most views on YouTube were analysed. The analysis confirmed that the image of women in music videos is more sexualised and denigrated than that of men.